Surface‐water availability governs survival of an amphibian in arid mountain streams. (12th November 2018) - Zylstra, Erin R.; Swann, Don E.; Steidl, Robert J.
Abstract: Declines in amphibian populations worldwide have been linked to multiple factors, including recent changes in climate. Changes in precipitation, for example, can alter the availability of aquatic resources that are required by many amphibians for successful reproduction and larval development. Changes in climate have the potential to affect other important demographic parameters, particularly for species that are active year‐round. Therefore, we studied survival of post‐metamorphic (snout‐vent length ≥50 mm) lowland leopard frogs ( Lithobates yavapaiensis ) in arid mountain canyons, where surface water is limited and its availability can vary markedly within and among years. Between 2013 and 2015, we surveyed frogs 33–74 times in each of six stream reaches distributed across two catchments in southern Arizona and used capture–recapture methods based on in situ photographs to identify individuals. We used Cormack–Jolly–Seber models to explore how surface‐water availability, weather and vegetation influenced seasonal variation in apparent survival of post‐metamorphic individuals. Overall, mean annual apparent survival in this dynamic, arid environment was low ( ϕ ^  = 0.11, 95% confidence interval = 0.07–0.14). Survival varied with ambient temperature, dew point, perimeter groundcover and year, but especially with changes in surface‐water availability. When water levels were at or near 100% of maximum pool depths, mean monthly survival was high ( ϕ ^  ≥ 0.88); when water levels were at 50%, survival decreased modestly ( ϕ ^  = 0.81) and when at 20%, survival dropped sharply ( ϕ ^  = 0.36). A decrease in survival of post‐metamorphic frogs in response to severe drought almost certainly contributed to the extirpation of frogs from one catchment in 2015. We anticipate that predicted increases in frequency and severity of drought will decrease the probability that lowland leopard frogs persist in this region over the long‐term, as droughts are expected to increase local extirpations and limit the ability of individuals to disperse through an increasingly arid landscape.